All about meat - Skok, Stephen; Video Education Australasia (Australia : Video Educational Australasia, 2001)
This program look at how meat is presented for purchase to the consumer, showing what producers are doing to address dietary and health concerns
Title from title screen
Executive producer, Neil Barrett ; editor, Simon Wright ; graphics, Reece Sanders ; camera, Tim Mummery, Stephen Skok
Presenter: Andrea Waycott
Keywords: Meat cutting; Meat industry and trade; Meat cuts; Meat -- Quality; Meat hygiene